Rock burials in the dated 16th century (Studia Archaeologica, 2026)
Rock burial monuments are distributed across the Altai, Khangai, Khentii, and Gobi mountain ranges of Mongolia, representing a funerary tradition practiced by ancient nomads for approximately two millennia. The vast majority of discovered sites date back to the Middle Ages, specifically the 13th and 14th centuries. By this period, rock burial had already evolved into a well-established and widely practiced ritual, becoming one of the two primary forms of interment. This article examines two specific rock burials: one from the Shar bulag valley in Duut Soum, Khovd Province, and another from Avdrant khairkhan Mountain in Nomgon Soum, Umnugovi Province. Radiocarbon dating has identified these sites as belonging to the post-Imperial period, specifically the 16th century. The findings from these burials coincide with the era when Buddhism spread throughout Mongolia, leading to profound transformations in funerary customs. Thus, they serve as vital primary sources for the study of Mongolian burial culture during this transitional period. We have had samples from rock burials subjected to dating analysis (14C) in the the Ancient Protein and Isotope Laboratory at the University of Michigan. As a result, Shar bulag AD 1503-1598, median probability AD 1558. Avdrant khairkhan AD 1471-1634, median probability AD 1564. Briefly, in relation to time, mongol burials are classified into the early period, the classical period, and the late period. The two burials mentioned above belong to the late period category. It will be a source of contribution to the study of the burial culture of the Mongols of this era.XVI зууны үед холбогдох хадны оршуулгуудХураангуй. Хадны оршуулгын дурсгал нь манай улсын Алтай, Хангай, Хэнтий, Говийн уулсаар тархсан байдаг. Илэрч олдсон дурсгалын дийлэнх нь дундад зууны үе буюу XIII-XIV зууны үед холбогддог бөгөөд энэ үе гэхэд оршуулгын зан үйл нь нийтлэг ашигладаг оршуулгын хоёр хэлбэрийн нэг болж байжээ. Энэхүү өгүүлэлд Ховд аймгийн Дуут сумын нутаг Шар булгийн ам, Өмнөговь аймгийн Номгон сумын нутаг Авдрант хайрхан уул зэрэг хадны 2 оршуулга хамрагдсан ба АНУ-ын Мичиганы Их Сургуулийн “Ancient Protein and Isotope” лабораторид хийсэн радиокарбоны шинжилгээгээр XVI зууны үед холбогдох дурсгал болохыг тодорхойлсон юм. Тухайлбал, Шар булгийн амны оршуулга НТ 1503-1598 буюу дундаж магадлалаар 1558 он, Авдрант хайрхны оршуулга НТ 1471-1634 буюу дундаж магадлалаар 1564 оных гэж гарчээ. Он цагтай холбогдуулан товч өгүүлэхэд монголын үеийн булш оршуулгын дурсгалыг эхэн үе, сонгодог үе, хожуу үе хэмээн ангилан авч үздэг бөгөөд дээрх хоёр дурсгал хожуу үеийн ангилалд хамаарах ба Монголд Буддын шашны III удаагийн дэлгэрэх үйл явц өрнөж, оршуулгын зан үйлд гүнзгий өөрчлөлт орсон цаг үетэй мөн давхцаж байгаа төдийгүй эл үеийн монголчуудын оршуулгын соёлын судалгаанд хувь нэмэр бүхий эх сурвалж болох юм.          Түлхүүр үг: Хадны оршуулга, XVI зууны монголчууд, оршуулгын зан үйл, радиокарбоны шинжилгээ